When does dropping out of university become educational exclusion? (Innovaciones Educativas, 2023)
Often in the educational context, the terms dropping out and exclusion are homologated because of the deterioration suffered by the educational systems. However, both terms have a polysemic feature that generates ambiguity regarding the constructs they refer to. Therefore, this essay is a revision of the different definitions that have been coined to describe exclusion and withdrawal in educational contexts, aiming to identify when dropping out is a result of educational exclusion. We begin with the general concept of educational exclusion as the starting point, later spelled out according to its educational dimensions and linked to school withdrawal while appreciating both concepts' similarities, differences, and concomitances. Our main conclusion is that social and educational exclusion, more than a consequence of dropping out of university, is a cause, even though there are circumstances in which an early withdrawal from university increases the possibility of exclusion that generally comes afterward.
Keywords: education; social exclusion; higher education; dropping out; educational opportunity; school failure